2021
DOI: 10.1002/cbe2.1260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nursing students’ research competencies with competency‐based education

Abstract: Introduction There is a preponderance of studies on nurses’ research competency and its benefits to the nursing profession. However, investigations on nursing students’ research competency in the context of competency‐based education (CBE) remain underreported. Objective This study investigated the predictors and associations of Saudi nursing students’ research competencies using CBE approach. Methods This research used a descriptive, cross‐sectional design. A total enumeration sampling or census of 347 nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…By contrast, Bamila N et al (29) found that more than half of nursing students had adequate level of knowledge in nursing research. Moreover, Grande et al (33) found that most nursing students were aware with the nursing research.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Bamila N et al (29) found that more than half of nursing students had adequate level of knowledge in nursing research. Moreover, Grande et al (33) found that most nursing students were aware with the nursing research.…”
Section: Discussionmentioning
confidence: 99%
“…The CBE entails defining the learning outcomes and integrating theory and skills and the assessment approaches (Van Melle et al, 2019). Various teaching-learning and assessment strategies that promote student-centeredness are also adopted to enhance deep learning (Frank et al, 2010;Grande et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Competency‐based education is a strategy that aims at preparing graduates on competencies to meet the population's health needs (Frank et al, 2010 ; Grande et al, 2021 ). The educational strategy advocates third‐generation reforms emphasising the need for competency attainment, which focuses on addressing the population's health needs.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Therefore, this concept or system of competency standards is now applied to answer the weaknesses of conventional learning approaches that have been implemented for many years but are not able to answer the problem of the need for manpower. Competence is to compare or integrate knowledge and expertise and its application in working by the required performance standards [23]. This means that a person who has enough knowledge and expertise without application in the attitudes or behaviors expected at work.…”
Section: Student Skills Before and After Learning Competent-based Cur...mentioning
confidence: 99%